Narrativas de amor e luta : a constituição da oficialidade da monogamia e a luta contra a subjugação das mulheres - Freitas, Monique Amaral de (Universidade Federal de São Carlos, 2016)
In this dissertation it proposes to understand how is discursively constituted the relationship between monogamy and the subjugation of women. For that, it bases the theoretical assumptions developed by the Bakhtin Circle, guiding me in a dialogical perspective of language. In addition, over the analysis it establishes a link between the feminist theories of Simone de Beauvoir (1949/2015), Heleieth Saffioti (1996/2015), Ivone Reimer (2005), among others. Firstly, it analyzes how the official status of monogamy is constituted in the discourses of social institutions, here defined as the Church, the State and the media. In order to think the Christian religious discourse, it analyzes passages from the Holy Bible and the leaders' statements from the Catholic, Evangelical and Pentecostal denominations about marriage and the affective-sexual relationships. Regarding the State, it discusses through the Federal Constitution and two Law Projects how family and marriage are defined. Posteriorly, through discussion of some media products, especially the films Snow White (1938) and Fifty Shades of Grey (2015), it discusses how the media constitute monogamy as the official discourse. In the second chapter, it discusses historical data provided by the work História do amor no Brazil (2005/1015), by Mary Del Priore, and documents produced by the feminist movement of the second wave, to understand how the discursive changes in the official models of affective-sexual relationships changes the women's lives. In the third and last chapter, it discusses how is constituted the relationship among affective-sexual relationships models and the domination of women using three texts of self-described feminist blogs. After discussing the texts, it concludes that monogamy is constituted as a way of subjugating women because it has incorporated male domination into the core of it's official discourse. Therefore, the relationship between the discursive constitution of the official status of affective-sexual relationship models and female subjugation is related to the discourse of male domination, not the monogamy itself.
Keywords: Feminismo; Linguagem; Monogamia; Discurso; Amor; Discourse; Monogamy; Women; Feminism; Official ideology; Language; LINGUISTICA, LETRAS E ARTES::LINGUISTICA